Issues in Macroeconomic Policy and Financial Management in Nigeria: essays in honour of Prof. Ndubuisi I. Nwokoma - Omojolaibi, Joseph A.; Eregha, Perekunah B.; Taiwo, Abayomi E. (Lagos Academic Publishing Centre, University of Lagos, 2024)
The book is a compendium of quality articles from some of the best scholars around, as well as write-ups from products of the Centre for Economic Policy Analysis and Research (CEPAR), University of Lagos. The chapters of the book are written by scholars and up-coming public financial management practitioners who have appreciated the immense contributions of Prof. Ndubuisi Nwokoma to economic policy analysis and research, especially in the area of macroeconomic policy, financial economics and public financial management.
Includes bibliographical references
osc 30/05/24
Loans
Keywords: Macroeconomic policy; Financial Management; Nigeria